Control of the neurovascular coupling by nitric oxide-dependent regulation of astrocytic Ca2+ signaling - Muñoz, Manuel F.; Puebla, Mariela; Figueroa, Xavier F. (Frontiers in Cellular Neuroscience, 2015)
Neuronal activity must be tightly coordinated with blood flow to keep proper brain function, which is achieved by a mechanism known as neurovascular coupling. Then, an increase in synaptic activity leads to a dilation of local parenchymal arterioles that matches the enhanced metabolic demand. Neurovascular coupling is orchestrated by astrocytes. These glial cells are located between neurons and the microvasculature, with the astrocytic endfeet ensheathing the vessels, which allows fine intercellular communication. The neurotransmitters released during neuronal activity reach astrocytic receptors and trigger a Ca2+ signaling that propagates to the endfeet, activating the release of vasoactive factors and arteriolar dilation. The astrocyte Ca2+ signaling is coordinated by gap junction channels and hemichannels formed by connexins (Cx43 and Cx30) and channels formed by pannexins (Panx-1). The neuronal activity-initiated Ca2+ waves are propagated among neighboring astrocytes directly via gap junctions or through ATP release via connexin hemichannels or pannexin channels. In addition, Ca2+ entry via connexin hemichannels or pannexin channels may participate in the regulation of the astrocyte signaling-mediated neurovascular coupling. Interestingly, nitric oxide (NO) can activate connexin hemichannel by S-nitrosylation and the Ca2+-dependent NO-synthesizing enzymes endothelial NO synthase (eNOS) and neuronal NOS (nNOS) are expressed in astrocytes. Therefore, the astrocytic Ca2+ signaling triggered in neurovascular coupling may activate NO production, which, in turn, may lead to Ca2+ influx through hemichannel activation. Furthermore, NO release from the hemichannels located at astrocytic endfeet may contribute to the vasodilation of parenchymal arterioles. In this review, we discuss the mechanisms involved in the regulation of the astrocytic Ca2+ signaling that mediates neurovascular coupling, with a special emphasis in the possible participation of NO in this process.